Evaluasi Kualitas Visual Lanskap Pada Kawasan Wisata Pantai Sendang Biru Kabupaten Malang - Lobalita Fatima Da Silva; Debora Budiyono; Hendra Kurniawan (Universitas Trisakti, 2024)
Evalution Of Landscape Visual Quality In The Sendang Biru Beach Tourism area Malang Regency. Malang Regency has coastal waters with natural phenomena that have the potential to be tourist attractions, such as waterfalls and wide expanses of white sand beaches. The tourism potential can be used to support regional development based on tourism. The policy in the Malang Regency Tourism Development Master Plan in 2005 states that tourism planning aims to make Malang Regency one of the tourist destinations in the regional scope, at least in the scope of East Java with its development strategy, namely improving several tourist attractions to become mainstay tourist destinations so that the desired target can be achieved. Through the potential of Sendang Biru, the Malang Regency government developed this area as a fisheries industry area while developing it into a tourist destination (LPPD. Malang Regency Government 2014 As a tourist area, of course Sendang Biru Beach must be managed as well as possible to maintain its sustainability both from the physical biophysical and tourism systems, suitability for humans and nature. The research to be conducted uses the Scenic Beauty Estimation (SBE) method as a method of estimating aesthetic quality through comparison, in the form of recommendations in using the theory of elements and design principles.